Stylistic features of director Tim Burton (Journal of the College of Basic Education, 2025)
Stylistic features constitute one of the dominant concerns within the filmic fabric, and their manifestations vary in their embodiment of the elements of cinematic language, according to the artistic vision and the particular style the artist infuses into the film. Furthermore, the aesthetic, philosophical, intellectual, and technical influence of artistic styles and their reflections on the formation and characteristics of style have produced contemporary directorial visions that have effectively enriched the cinematic screen, particularly the works of American director Tim Burton, who has a distinctive style all his own. The methodological framework included an introduction that was defined by posing the following question: What are the stylistic characteristics of director Tim Burton? The theoretical framework included two sections: the first, entitled Stylistic Characteristics of Contemporary American Cinema, in which the researcher addressed the most prominent stylistic characteristics of some contemporary American directors. The second section, titled Tim Burton's Role in Cinema, discussed the stylistic characteristics of the American director's works and his role in cinema in general. The researcher then addressed the theoretical framework's indicators. The research procedures defined her research community as intentional samples from director Tim Burton's films and relied on the descriptive approach in analyzing her research samples, namely the film Sweeney Todd. The research tool was formed based on the theoretical framework and was subjected to a committee of experts in the field of specialization in order to complete the research procedures and analyze the sample, and then arrive at the results, the most prominent of which are:1. The exotic decor and setting are stylistic characteristics of director Burton with a fantasy character, especially in the sets and scenes in the films Sleepy Hole and Sweeney Todd (research sample). The most important conclusions are:1- Director Tim Burton's stylistic features represent one of the contemporary stylistic trends in both form and content in world cinema